Sistem Pendukung Keputusan untuk Rekomendasi Kelulusan Sidang Skripsi Menggunakan Metode AHP-TOPSIS - Desi Ratna Sari; Agus Perdana Windarto; Dedy Hartama; Solikhun Solikhun (Jurnal Teknologi dan Sistem Komputer, 2018)
This research proposes a decision support system in determining thesis exam graduation using AHP and TOPSIS method. The AHP method weighted the criteria to generate values for each criterion, in which the value of each criterion was used to obtain a ranking of some alternatives with TOPSIS. The criteria used for the assessment are 5 chapters (C1), neatness (C2), manners (C3), material delivery (C4) and material mastery (C5). Merging the AHP and TOPSIS methods can optimize the weighting of criteria values that affect the more objective alternative ranking results. The resulting Hamming distance is 96.2% and the Euclidean distance is 0.8096 for 95 students.